Employee Retention Factor at IT Startup Company: Job Satisfaction as Mediating Variable - Ahmad Azmy; Antoni Ludfi Arifin (Media Ekonomi dan Manajemen, 2025)
This study analyzes factors that have implications for employee retention in IT-Startup companies. This study aims to explain factors that contribute to employee retention with job satisfaction as a mediating variable. Employer branding, psychological contract, organizational commitment and job environment are predictors of employee retention. This quantitative study applied a purposive sampling technique, involving 350 employees in IT startup companies as respondents. They were employees who have worked for the company for at least 3 years, held at least a staff-level position, and work in an IT startup company. Data were analyzed using Structural equation modeling (SEM) to depict the direct and indirect effects of the factors on employee retention. Job satisfaction was examined as the mediating variable. The study showed that the employer branding, organizational commitment, and job environment directly affected employees’ job satisfaction. These three variables also indirectly affected employee retention. Meanwhile psychological contract was found not to directly affect employees’ job satisfaction and not to indirectly affect the employee retention IT startups are recommended to improve their psychological contract in order to enhance the employees’ job satisfaction. Employees’ professionalism and contribution are pivotal in improving the company’s business quality. Organizations should be able to meet employees’ need comprehensively according to the business achievement.